NT-36 FOCUSED ULTRASOUND ENHANCED CHEMOTHERAPEUTIC AGENT (TEMOZOLOMIDE) DELIVERY FOR BRAIN TUMOR TREATMENT: A PRECLINICAL INVESTIGATION - Wei, Kuo-Chen (Oxford University Press, 2014)
Malignant brain tumor is highly aggressive disease with high recurrence and motility rate. Current therapeutic approaches including surgery, radiation and chemotherapy only provide limited disease progression control. One of the major issues results its poor outcome is the blockade of chemotherapeutic agent delivery by the blood-brain barrier (BBB). Recently, focused ultrasound (FUS) with the presence of microbubbles has been confirmed its feasibility in transient and local BBB opening, demonstrated the potential in performing noninvasive brain drug delivery. Therefore, the use of FUS for enhancement of drug delivery to brain parenchyma may serve as a possible treatment of brain tumors. The objective of this study is to investigate the potential in combining the FUS-induced BBB opening with the Temozolomide (TMZ), the first-line brain tumor chemotherapeutic agent, to improve the brain tumor treatment. Brain tumor bearing mice were served as the animal model. Evans-blue was administered to demonstrate the blood-brain BBB-opened site, quantification of TMZ concentration in brain and tumor tissue was performed by high performance liquid chromatography (HPLC) and electrospray ion trap mass spectrum. Our results revealed the accumulation of TMZ in tissue or cerebrospinal fluid of FUS exposed groups is significantly increased as compared with controlled group, which demonstrates the efficacy of FUS-BBB opening for enhancement of local TMZ delivery in brain. Furthermore, FUS-BBB opening combines TMZ treatment significantly inhibits the tumor growth rate and prolongs the median survival of brain tumor animals. Our study provide evidences supporting the effect of FUS-BBB opening in enhancement of local delivery of chemotherapeutic agent to brain and the potential for future clinical application.